THE EFFECTIVENESS OF GRAMMAR TRANSLATION METHOD IN TEACHING READING AT FIFTH SEMESTER OF AHWAL ASSYAKHSIYAH OF STIS DARUL FALAH MATARAM: English - Zul karnain; Bidarita Widiati (Prodi Tadris Bahasa Inggris, 2021)
AbstractThis research was conducted to investigate the effect of using GrammarTranslation Method (GTM) in teaching reading at fifth semester students ofAhwal As-Syakhsiyah of STIS Darul Falah Mataram in academic year2018/2019. This research was an experimental research with two groupdesign. The population of this research was all of students at fifth semester ofAhwal As-Syakhsiyah of STIS Darul Falah Mataram which consisted of 60students and they were divided into 2 classes, Class A and B. Class A wastaken as sample by using cluster sampling technique. Pre-test and post-testwere used in collecting the data. Then, it was analyzed by using ttest. Theresult showed that score of t-test (3.63) was higher than the score of t-table(2.003) at the confidence level .05 (95%). Therefore, null hypothesis (H0)which stated that “GTM is not effective in teaching reading’’ was rejected.Meanwhile, the score of t-test (3.63) was higher than the score of the t-table(2.663) at the confidence level .01 (99%). It indicates the alternate hypothesis(Ha) which stated that “GTM is effective in teaching reading’’ was accepted.It means that there was a significant effect of using GTM in teaching readingtext because there was a significant difference between students’ pre-test andpost-test score after treatments. Furthermore, the results of tests show thatmost students gave positive responses toward the use of GTM. Finally, theresult of the research suggest that the students loved this method because itsuccessfully motivated them to read texts in an enjoyable way and to improvetheir reading texts in terms of enriching vocabularies, organizing ideas andunderstanding the text easily. It is then recommended that GTM be used inteaching reading in different text types and levels of schooling.Key words: Grammar Translation Method, Descriptive text, Reading